The EU's response vs. Chinese vaccine diplomacy in Central and Eastern Europe - Goran ILIK; Vesna SHAPKOSKI (Eastern Journal of European Studies, 2022)
This paper analyses the initial critical points of the EU's weakness in quickly responding to the crisis and the Chinese assertiveness in using vaccine diplomacy to achieve European political objectives. With the case study based on indicative research on public opinion, the paper provides a more profound understanding of the impact of Chinese-related activities in the CEE region, particularly concerning EU coherence and solidarity. The paper concludes that the Chinese presence in Europe via "vaccine diplomacy" threatens the unity of the EU and the CEE region.